Effects of silybin supplementation on growth performance, serum indexes and liver transcriptome of Peking ducks - Zhang, Ziyue; Shi, Bozhi; Lv, Xueze; Dong, Yingchao; Li, Lei; Xia, Zhaofei (Frontiers in Veterinary Science, 2024)
As an emerging feed additive extracted from the traditional herb milk thistle, silybin has few applications and studies in Peking ducks. The aim of this study was to explore the practical significance of silymarin application in Peking ducks and to provide more theoretical support for the application of silymarin in livestock and poultry production. A total of 156 1-day-old healthy Peking ducks were randomly divided into four groups and supplemented with 0 mg/kg (control group), 400 mg/kg (S400), 800 mg/kg (S800) and 1600 mg/kg (S1600) of silybin in the diets at day 14, to investigate the effects of silymarin on the growth, serum indexes and liver transcriptome of Peking ducks. The whole experiment lasted until day 42, and the sample collection was scheduled to take place in the morning. A substantial inprovement in average daily gain (ADG) and a decrease in feed conversion ratio (FCR) occurred in the S1600 group on days 14-28 compared to the control group (p ＜0.05). The FCRs of other additive groups in the same period showed the same results. Supplementation of diets with silybin significantly increased serum IgA levels and when 1600 mg/kg of silybin was given, levels of TNF-α and IL-6 were also significantly decreased. (p＜0.05). In addition, we observed that the S1600 group had a significantly lower (p < 0.05) glutamine transaminase and an increased (p < 0.05) T-SOD level in the S400 group (p＜0.05). Liver transcriptome sequencing showed that 71 and 258 differentially expressed genes (DEGs) were identified in the S400 and S1600 groups, respectively, compared with the control group. DEGs related to cell composition and function, antigen processing and presentation were up-regulated, while DEGs related to insulin resistance and JAK-STAT were down-regulated. Conclusively, silybin can be used as a feed additive to improve the growth performance and health status of Peking ducks.